THE IMPACT OF FINANCIAL INCLUSION OF MIGRANTS ON ECONOMIC GROWTH - CHERNOBAY, Liana; MALIBRODA, Sviatoslav (Scientific journal «World of Finance», 2024)
Introduction. In the global economy, people migrate between regions or countries in searching better life. The migration is beneficial for both the country of origin and the host country. Economic benefits consist in sending money by migrants’ home through various remittance channels such as commercial banks, cash money market, electronic transfers. That is why the lack of access to regular financial services is a significant challenge to the economic independence of migrants and their self-sufficiency. As a result, international humanitarian organizations are increasingly promoting the financial integration of refugees, their empowerment, integration into the host economy, promoting self-sufficiency and financial inclusion. This actualizes the scientific research of economic growth and financial inclusion of migrants, because a passive response to the problem threatens the harmonious development of regions that are actively involved into migration processes.The purpose of the article is the research with focus to analyze the constituent elements of economic growth in the conditions of migration flows increasing and to outline directions for strengthening the financial inclusion of migrants.Results. The constituent elements of economic growth in the conditions of financial inclusion of migrants were considered. It was provided a taxonomic analysis of the theories of migration, its motivation and attraction factors. The Ukrainian economy was analyzed under of migration flows growing, estimated the pace of its recovery and reconstruction due to international aid and remittances from migrants. It was evaluated the financial integration and financial inclusion of migrants in terms of the availability of basic financial services. The factors affecting the financial inclusion of migrants and preventing the receipt of financial services were identified. It was outlined the directions for strengthening the financial inclusion of migrants.Prospects. The subject of further scientific research is the research of the level of digital financial inclusion of migrants, which can become an effective tool for overcoming socio-economic problems and stimulating economic development.